2013
DOI: 10.1186/1471-2474-14-145
|View full text |Cite
|
Sign up to set email alerts
|

The six-minute walk test is an excellent predictor of functional ambulation after total knee arthroplasty

Abstract: BackgroundThe Six-minute walk (6MW) and Timed-Up-and-Go (TUG) are short walk tests commonly used to evaluate functional recovery after total knee arthroplasty (TKA). However, little is known about walking capacity of TKA recipients over extended periods typical of everyday living and whether these short walk tests actually predict longer, more functional distances. Further, short walk tests only correlate moderately with patient-reported outcomes. The overarching aims of this study were to compare the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 39 publications
8
84
2
5
Order By: Relevance
“…Equations were developed taking into account sex, age, height, and weight, which were determined to be important factors accounting for roughly 40 % of the variance in distance walked. Similar reference values have been found in more recent studies in healthy individuals [5,25,26].…”
Section: Question 4: What Is the Target Goal Value?supporting
confidence: 90%
“…Equations were developed taking into account sex, age, height, and weight, which were determined to be important factors accounting for roughly 40 % of the variance in distance walked. Similar reference values have been found in more recent studies in healthy individuals [5,25,26].…”
Section: Question 4: What Is the Target Goal Value?supporting
confidence: 90%
“…Due to its simplicity and close relation to activities of daily living, the 6MWT has been used to represent functional capacity in chronic obstructive pulmonary disease and total knee arthroplasty patients and older individuals [1][2][3]. Conversely, measures of gait variability are more specific indicators of the neural control of gait [4] and have been used to discriminate between older fallers and nonfallers and to predict older adults at risk of falling, a major health hazard in this population [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The TUG test has acceptable concurrent validity for measuring dynamic balance and high repeatability in patients awaiting TKA 18) . Similarly, Ko et al 33) found that TUG test predicted physical activity and WOMACFunction scores. The association between TUG test and postoperative gait speed may be due to their sit-to-stand element; TUG test performance depends on a combination of neuromuscular components (walking ability, lower limb strength, and balance) that also play important roles in gait speed.…”
Section: Discussionmentioning
confidence: 83%
“…Along with gait speed, the 6MWT is commonly used to evaluate ambulatory capacity because it is a simple and clinically relevant measure of exercise endurance. The 6MWT has been shown as a robust measurement of functional mobility during the long-term recovery of patients after TKA 33) and is a highly reliable measurement tool in patients who underwent primary TKA 34) . Here, we found that preoperative BMI was the most powerful predictor of postoperative gait endurance in the first month following TKA.…”
Section: Discussionmentioning
confidence: 99%